OPTIMALISASI SUMBER DAYA KOMPUTER DENGAN VIRTUALISASI SERVER MENGGUNAKAN PROXMOX VE - Afdhil Hafid; Soni Soni; Abdurrahman Abdurrahman (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2019)
Virtualization technology is a topic that began to be scrutinized by researchers. This is inseparable from the technology's ability to reduce the cost of providing infrastructure and operations independently for each service to be served. With server virtualization, we can make several computers into one, which used to be possible for server computers to have three physical computers that can be used as one for the three server computers which in fact the resources on a single physical server computer will not use all the resources in one single physical computer. The existence of proxmox, then all servers can be connected in a network together so that they are able to streamline time. In addition, Proxmox has a web console that can be used for various purposes in server virtualization and maintenance. In this study, the performance of server virtualization using ProxmoxVE will be examined. This study is intended to determine the load of memory usage, load the CPU when running all the servers in Proxmox, and examine the Throughput, PacketLoss, Delay and Jitter on the server. Keyword: Proxmox, Virtualization, Resources, Server, Operating System